ANALYSIS OF DELAYS IN BUDGET ABSORPTION IN THE ASAHAN DISTRICT HEALTH DEPARTMENT NORTH SUMATRA PROVINCE - Dicky Muhammad Rahim Nasution; Tengku Irmayani; Muhammad Husni Thamrin (PT. Radja Intercontinental Publishing, 2024)
The delay in budget absorption that occurred at the Asahan District Health Service was due to several causes. The research objectives to be achieved from this research are analyzing the Work Plan and Budget with the realization of activities, analyzing factors that influence budget realization at the end of the year, and analyzing the consequences of budget delays that occur at the Asahan District Health Service in the 2023 budget year. Researchers use qualitative research with explanatory methods. The findings that can be conveyed in the results of this research include: adjustments to the Work Plan and Budget with the realization of activities for the 2023 fiscal year at the Asahan District Health Service due more to the budget process. This means a budget policy with the principle of quality and targeted spending. Apart from that, the realization of the budget at the end of the year that occurred at the Asahan District Health Service was more due to technical instructions, human resource capacity, especially knowledge of PMK212 regulations, and budget sources such as PAD that was not reached targets and provisions of transfer funds from the center that were not in accordance with the schedule. Consequences of budget delays at the Asahan District Health Service, which can reduce the budget ceiling in the following year and results in activities not being realized.